Fabrication of double‐cladding Ho3+/Tm3+ co‐doped Bi2O3–GeO2–Ga2O3–BaF2 glass fiber and its performance in a 2.0‐μm laser. Issue 8 (22nd February 2019) - Zhou, Dechun; Jin, DanYang; Ni, Qiming; Song, Xiangyang; Bai, Xuemei; Han, Kexuan
Abstract: A novel double‐cladding Ho 3+ /Tm 3+ co‐doped Bi2 O3 –GeO2 –Ga2 O3 –BaF2 glass fiber, which can be applied to a 2.0‐μm infrared laser, was fabricated by a rod‐tube drawing method. The thermal properties of the glass were studied by differential scanning calorimetry. It showed good thermal stability and matching thermal expansion coefficient for fiber drawing when T x − T g  > 193°C and the maximum difference of the thermal expansion coefficient is 3.55 × 10 −6 /°C or less. The 2.0‐μm luminescence characteristics were studied using the central wavelength of 808 nm pump light excitation. The results show that when the concentration ratio of Ho 3+ /Tm 3+ reaches 0.5 mol%:1.0 mol%, the maximum fluorescence intensity was obtained in the core glass, the emission cross section reached 10.09 × 10 −21  cm 2, and the maximum phonon energy was 751 cm −1 . In this paper, a continuous laser output with a maximum power of 0.986 W and a wavelength of 2030 nm was obtained using an erbium‐doped fiber laser as a pump source in a 0.5 m long Ho 3+ /Tm 3+ co‐doped glass fiber. In short, the results show that Ho 3+ /Tm 3+ co‐doped 36Bi2 O3 –30GeO2 –15Ga2 O3 –10BaF2 –9Na2 O glass fiber has excellent laser properties, and it is an ideal mid‐infrared fiber material for a 2.0‐μm fiber laser with excellent characteristics